Intravenous Infusion of Cereport Increases Uptake and Efficacy of Acyclovir in Herpes Simplex Virus-Infected Rat Brains - Bidanset, Deborah J. (American Society for Microbiology, 2001)
The outcome of herpes simplex virus (HSV) infections manifesting as encephalitis in healthy or immunocompromised individuals is generally very poor with mortality rates of about 8 to 28% with treatment. The long-term prognosis of survivors is often problematic, posing the need for alternative treatments that may decrease the mortality and morbidity associated with herpes encephalitis. This study addresses one such approach that includes a temporary permeabilization of the blood-brain barrier during treatment with acyclovir (ACV). In these studies we utilized a synthetic bradykinin analog, Cereport (RMP-7), in conjunction with ACV to treat HSV infection of the brain in a rat model. Cereport, infused intravenously via the jugular vein, was shown to increase [(14)C]ACV uptake in both the HSV-1-infected and -uninfected rat brain by approximately two- to threefold, correlating with enhanced efficacy of ACV in various brain compartments. In another series of experiments to determine efficacy, various doses of unlabeled ACV were administered during infusion with RMP-7. The decrease in viral titers in the temporal regions of the brain after 5 days of treatment suggested that this approach enhanced the efficacy of ACV treatment. These data indicated that Cereport infused with ACV enhances both the penetration and efficacy of this drug in the treatment of an experimental HSV-1 infection of the rat brain.